A chemometrics-assisted excitation–emission matrix fluorescence method for simultaneous determination of arbutin and hydroquinone in cosmetic products. Issue 24 (8th June 2016) - Zhu, Li; Wu, Hai-Long; Xie, Li-Xia; Fang, Huan; Xiang, Shou-Xia; Hu, Yong; Liu, Zhi; Wang, Tong; Yu, Ru-Qin
Abstract : Simultaneous determination of arbutin and hydroquinone in cosmetic products using a second-order calibration method coupled with excitation–emission matrix fluorescence. Abstract : A fast analytical method that combines second-order calibration based on alternating trilinear decomposition (ATLD) algorithm with excitation–emission matrix (EEM) fluorescence technique is proposed to mathematically separate the overlapped spectra and simultaneously quantify arbutin (AR) and hydroquinone (HQ) in cosmetic products. This method inherits the merit of high sensitivity of traditional fluorescence and fully realizes the "second-order advantage". For AR and HQ, the calibration ranges are 40.00–400.00 and 20.00–200.00 ng mL −1, respectively. The limits of detection for both analytes are in the range of 1.51–4.01 ng mL −1 . The proposed method could be applied to diluted samples of different cosmetic products with satisfactory results. The actual concentrations of AR in the tested cosmetic products are found to be in the allowable concentration range (7%); while, the prohibited skin whitening agent HQ is detected in lotion. The contents of AR and HQ in the tested cosmetic products obtained by the proposed method are also in accordance with those of the validated high-performance liquid chromatographic method. These satisfactory results indicate that the proposed method has the potential to accurately quantify AR and HQ in complex matrices containing uncalibrated interferents, and shows promise as a reliable tool for quality monitoring of cosmetic products.